Reimagining Arabic Learning in Aceh’s Pesantren for a Sustainable Future - Kurniawan Arif Maspul; Muhammad Taha; Hasbi Yusron (Frontiers in Research Journal, 2025)
In Aceh Besar, Pesantren face a crucial challenge: maintaining Arabic as a vibrant religious medium while preparing students for a digital, interconnected world. This paper introduces an integrative model that rejuvenates traditional teaching methods through communicative, task- based techniques and context- aware technologies—localised LMS platforms and mobile-mediated interaction—rooted in Acehnese wisdom and Islamic ethics. It combines empirical and theoretical insights to show how blended learning, teacher professional development, competency-based assessment, and community-engaged curricula work together to enhance linguistic skills, learner motivation, and critical literacy. Comparative insights from Malaysia and Türkiye highlight scalable practices—such as national digital content archives, teacher exchange programs, and competency frameworks—that balance local authenticity with international standards and UNESCO's Education for Sustainable Development. Policy recommendations focus on infrastructure development, ongoing in- service training, curriculum reform that integrates sustainability themes into Arabic instruction, and public–private partnerships to democratise access and support innovation. The model emphasises sustainability across social, economic, and ecological dimensions, positioning pesantren as communities of civic engagement, environmental stewardship, and ethical leadership. The article argues that by viewing modernisation as cultural stewardship rather than cultural displacement, Arabic proficiency can extend beyond ceremonial mastery to serve as a tool for scholarship, civic engagement, and global dialogue. The roadmap provides practical, culturally relevant steps for policymakers, educators, and communities to transform Aceh's boarding schools into resilient, globally respected centres of Islamic learning.